Adaptación del perfil PERMA de bienestar subjetivo para adultos mayores institucionalizados colombianos - César Augusto Hernández Suárez; Viviana Hernández Vergel; Raúl Prada Núñez (Universidad Francisco de Paula Santander, 2018)
Objective: To adapt the PERMA profi le (Positive Emotions, Engagement, Relationship, Meaning and Accomplishment) of Butler & Kern through its application to a sample of institutionalized older adults living in the city of Cúcuta and the use of psychometric tests. Materials and method: It was part of the adaptation to Spanish made by Tarragona, was contextualized and the fi nal version was applied to a random sample of thirty institutionalized adults in Asylums of the city of Cúcuta, Colombia belonging to a population conformed by fi ve institutions with an approximate 250 subjects. The ability to discriminate items and their reliability was studied. Results: The internal consistency (α = 0.95) for the total scale was high. Conclusions: The PERMA profi le is a useful tool for assessing subjective well-being among institutionalized older adults in the city of Cúcuta, Colombia